Nutrient Dynamics in Cotton Leaf Tissues as Affected by Zinc Fertilization and Ontogeny: Nutrient Dynamics in Cotton Leaf Tissues - Ahmed, Niaz; Abid, Muhammad; Qayyum, Muhammad Farooq; Ali, Muhammad Arif; Hussain, Shahid; Noreen, Sibgha (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2016)
Plant-tissue analyses are performed to assess plant nutrient status, and to determine fertilizer requirements of the current and the future crop grown in the field. Application of zinc (Zn) fertilizer may increase or decrease levels of other nutrients in the crop plants. Field experiments were conducted during 2004 and 2005 to study the effect of Zn fertilization on nutrient concentrations in leaf-tissues of cotton plants at different growth stages. Five rates of Zn (i.e., 0.0, 5.0, 7.5, 10.0 and 12.5 kg Zn ha−1) were applied as ZnSO4·7H2O, in a randomized complete block design, with four replications. All plots were uniformy supplied (in kg ha-1) with 150 nitrogen (N) as urea, 60 phosphorus (P) as triple superphosphate, 50 potassium (K) as potassium sulfate and 1.0 B as borax. Most recent fully expanded leaves (without petioles) from the main stems were sampled 30, 45, 60, 90, 120 days after planting of the crop and the plant tissues were analyzed for N, P, K, calcium (Ca), magnesium (Mg), Zn, iron (Fe), manganese (Mn), and copper (Cu). Concentrations of Fe, Mn, Cu and P in leaves decreased significantly with Zn application indicating that optimum levels of these nutrients must also be maintained along with Zn application especially under marginal levels of these nutrients in soils. Leaf concentrations of the studied macro- and micro-nutrients, except K, increased with advancement of plant growth up to 60 days after sowing and then decreased gradualy. Observed concentrations of nutrients in cotton leaves at different critical stages will help in focusing future research aimed at defining critical nutrient concentrations at different stages of cotton.